Pengaruh Model Pembelajaran Integrated Lerning Terhadap Hasil Belajar Siswa Kelas 5 SDN 4 Gereneng - Anggraini, Febrian; Kudsiah, Musabihatul; Wardani, Iwan Usma (Program Studi Pendidikan Masyarakat, 2026)
Abstract: This study aims to determine the effect of using the Integrated Learning model on the learning outcomes of 5th grade students at SDN 4 Gereneng in the 2024/2025 academic year. The type of research used is experimental with a one group pretest-posttest design. Sampling was carried out using purposive sampling technique. The subjects of this study were 20 students. The research instrument given was a multiple-choice test. The prerequisite test used was the Liliefors test to examine the normality of the data. Based on the results of the normality test, it was found that the population was normally distributed. Based on the pretest-posttest results, it was seen that the average pretest score of students’ learning outcomes was 40.5 and the average posttest score was 82. From the results of the hypothesis test calculation of students’ learning outcomes using the t-test, it was found that tcount > ttable, namely 11.492 > 2.093, consulted on the table with db = N-1 (20-1) = 19, at a significance level of 0.05. Thus, Ho is rejected and Ha is accepted. This shows that the implementation of the Integrated Learning model affects the learning outcomes of 5th grade students at SDN 4 Gereneng Academic Year 2024/2025. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model pembelajaran Integrated Learning terhadap hasil belajar siswa kelas 5 SDN 4 Gereneng Tahun ajaran 2024/2025. Jenis penelitian yang digunakan adalah eksperimen dengan desain one group pretest-posttest design. Pengambilan sampel dilakukan dengan cara teknik porfosive sampling. Subyek penelitian ini adalah 20 siswa. Instrumen penelitian yang diberikan berupa tes pilihan ganda. Uji prasyarat yang digunakan adalah uji Liliefors untuk menguji normalitas data. Berdasarkan hasil uji normalitas diperoleh bahwa populasi berdistribusi normal. Berdasarkan hasil penelitian pretets-posttes terlihat nilai rata-rata pretests hasil belajar siswa adalah 40,5 dan nilai rata-rata posttest 82. Dari hasil perhitungan uji hipotesis tes hasil belajar siswa yang menggunakan uji t didapatkan hasil yaitu thitung > ttabel yakni 11,492 > 2,093 dikonsultasikan pada tabel tes hasil dikonsultasikan pada tabel db = N-1 (20-1) = 19, dengan taraf signifikansi 0,05. Dengan demikian Ho ditolak dan Ha diterima. Hal ini menunjukkan bahwa implementasi model pembelajaran Integrated Learning berpengaruh terhadap hasil belajar siswa kelas 5 SDN 4 Gereneng Tahun Ajaran 2024/2025.